α-Glucosidase inhibitory potential of Oroxylum indicum using molecular docking, molecular dynamics, and in vitro evaluation - Samhita Bhaumik; Alekhya Sarkar; Sudhan Debnath; Bimal Debnath; Rajat Ghosh; Magdi E.A. Zaki; Sami A. Al-Hussain (Elsevier, 2024)
Background: According to the International Diabetes Federation, there will be 578 million individuals worldwide with diabetes by 2030 and 700 million by 2045. One of the promising drug targets to fight diabetes is α-glucosidase (AG), and its inhibitors may be used to manage diabetes by reducing the breakdown of complex carbohydrates into simple sugars. The study aims to identify and validate potential AG inhibitors in natural sources to combat diabetes. Methods: Computational techniques such as structure-based virtual screening and molecular dyncamic simulation were employed to predict potential AG inhibitors from compounds of Oroxylum indicum. Finally, in silico results were validated by in vitro analysis using n-butanol fraction of crude methanol extracts. Results: The XP glide scores of top seven hits OI_13, OI_66, OI_16, OI_44, OI_43, OI_20, OI_78 and acarbose were -14.261, -13.475, -13.074, -13.045, -12.978, -12.659, -12.354 and -12.296 kcal/mol, respectively. These hits demonstrated excellent binding affinity towards AG, surpassing the known AG inhibitor acarbose. The MM-GBSA dG binding energies of OI_13, OI_66, and acarbose were −69.093, −62.950, and −53.055 kcal/mol, respectively. Most of the top hits were glycosides, indicating that active compounds lie in the n-butanol fraction of the extract. The IC50 value for AG inhibition by n-butanol fraction was 248.1 μg/ml, and for that of pure acarbose it was 89.16 μg/ml. The predicted oral absorption rate in humans for the top seven hits was low like acarbose, which favors the use of these compounds as anti-diabetes in the small intestine. Conclusion: In summary, the study provides promising insights into the use of natural compounds derived from O. indicum as potential AG inhibitors to manage diabetes. However, further research, including clinical trials and pharmacological studies, would be necessary to validate their efficacy and safety before clinical use.